Case Report: Clinical response of ensartinib for inflammatory myofibroblastic tumor of the urinary bladder with multiple metastases and TPM4-ALK fusion - Ren, Hongtao; Cheng, Qi; Chen, Xi; Sui, Dianjing; Zhang, Zhiyi; Chen, Fei (Frontiers in Oncology, 2025)
BackgroundInflammatory myofibroblastic tumor of the urinary bladder (IMTUB) is a rare tumor with low postoperative recurrence and metastasis. Due to the lack of clinical evidence, the optimal treatment paradigm for patients with IMTUB has not yet been established.Case presentationWe reported a case of a 55-year-old man who was diagnosed with bladder malignancy after transurethral resection of a bladder tumor, and then tumor metastasis was treated by traditional Chinese medicine. Following further disease progression, he was admitted to our hospital, where the diagnosis was revised to IMTUB with multiple metastases and TPM4–anaplastic lymphoma kinase (ALK) fusion by computed tomography (CT) scan, pathological diagnosis, immunohistochemistry, and genetic testing. The patient subsequently received 225 mg ensartinib once daily. Symptoms improved and achieved partial response (PR) with acceptable toxicities.ConclusionEnsartinib may provide a new therapeutic direction with promising efficacy and an acceptable safety profile for IMTUB with ALK fusion. Further clinical investigation is needed to identify its efficacy and safety.